Bioactive compounds in natural resources and the extraction methods in different types of solvents for various applications: a review - Rohayu, Jusoh; Nuramira Fateha, Sukor (2018)
The increasing demand of natural resources–based products in various fields such as cosmeceutical, pharmaceutical and food industries has created a great opportunities for the global marketing. Particularly, plants and herbs has been gaining attention from the researchers due to its tremendous benefits that possess anti–oxidant, anti–cancer, anti–microbial and anti–inflammatory effects. Aiming to study the functions of bioactive compounds in natural resources for various applications, certain issues were considered such as its benefits towards the skin and health. Besides, various extraction methods; conventional and non-conventional were discussed. Conventional extraction methods were basically the methods that have been actively implemented before, however it has few limitations. On the other hands, the non–conventional ones are the improved extraction methods that have been aggressively used in the recent studies. The details of the equipment along with the operating procedures, advantage and disadvantages of each method were compared. On top of that, a wide variation of solvents in the industrial processes has been actively used in reaction systems and separation such as water, organic solvent and the newly discovered green solvent, ionic liquid. In this study, along with the benefits of natural resources and the extraction methods, the wellness of solvents that were believed to play an important role in the extraction process as it helps in maximizing the extraction yield of bioactive compounds were also discussed in details